Okrasne sorte bukve (Fagus sylvatica L.) v Sloveniji - Puschner, Marko (Gozdarski vestnik, 2008)
This article introduces a determination key for ornamental cultivars of European beech. The key allows successful identification of 76 different cultivars. The data about cultivars that can be found in public places and specialized collections in Slovenia are also included. We recorded 16 different cultivars. Their list corresponds well to the list of the most common cultivars that can be found in public places and specialized collections in Europe.
Keywords: bukev; Fagus sylvatica L.; določevalni ključi